Eksplorasi Sebaran Penyakit Demam Berdarah Dengue (DBD) dan Pneumonia di Kota Malang - Swaidatul Masluhiya AF; Ragil Catur Adi Wibowo; Ahmad Luthfin (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Indonesia, as a country with a tropical climate, has a diverse prevalence of tropical diseases. Some tropical diseases that often occur in Indonesia such as dengue hemorrhagic fever (DHF) and pneumonia. This study aims to determine the distribution of DHF and pneumonia in Malang City from 2017-2020. This type of research is a descriptive study with the population and sample of patients with DHF and pneumonia in Malang City obtained from the Malang City Health Office from 2017 to 2020. The data collection technique used in this study was secondary data from the Malang City Health Office. The data that has been collected was then analyzed univariately using the Microsoft Excel program to describe the trend of cases of DHF and pneumonia in the last four years. Sukun District is the District with the highest incidence of DHF in Malang City, with 291 cases. In comparison, Blimbing District is the District with the highest pneumonia cases in Malang City, with a total of 1,914 patients. The highest chances of DHF and pneumonia in Malang City occurred in 2019 as many as 527 cases and 2,716 cases spread across 16 health centers and five sub-districts in Malang City.Keywords: DHF, Malang City, Pneumonia, spread